ALGAE-TECH an urban algae hub and innovation district for production, research, and development - Ong, Lianne Alexandra Y.; Balane, Ronald S. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
Rapid industrialization and urbanization are some of the key factors that contribute to global warming and greenhouse gas emissions, with cities playing a pivotal role in human impacts on the planet. With the worsening climate crisis and the increasing global demand for energy and resources, there is an urgent need to switch to renewable sources of energy and fuel before it is too late. Algae has gained worldwide attention as a new -bio-based energy source. Combined with its ability to sequester carbon dioxide and be used in widespread applications and byproducts--Algae is a key component of a new sustainable future, with spatial implications and potential integrations in the core of urban cities.
As Batangas City grows rapidly as a highly urbanized environment, it is well on its way to becoming the next worldwide gateway of the Philippines. In the wake of this, Batangas City struggles with the worsening pollution and congestion that is a result of this development. With the urbanization of the city, there is a need for a new way of thinking in the urban environment in order to adopt renewable and sustainable technologies, providing the community with access to more renewable resources and production technology. To drive this is an eco-urban catalyst in the form of Algae-Tech: a hub that integrated algae cultivation and production biotechnologies in the heart of an urban district, as an innovative urban space that aims to propagate the use of algae as the new technology and make algae cultivation viable within urban and industrial environments. The design vision for this project is to create a production, research, and innovation hub that serves to address sustainable and technological issues in the definition of contemporary public space.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Research facilities; Algae -- Batangas City